Reactive Oxygen Species in Autoimmune Cells: Function, Differentiation, and Metabolism - Lin, Weiji; Shen, Pan; Song, Yaqin; Huang, Ying; Tu, Shenghao (Frontiers in Immunology, 2021)
Accumulated reactive oxygen species (ROS) directly contribute to biomacromolecule damage and influence various inflammatory responses. ROS act as mediator between innate and adaptive immune cells, thereby influencing the antigen-presenting process that results in T cell activation. Evidence from patients with chronic granulomatous disease and mouse models support the function of ROS in preventing abnormal autoimmunity; for example, by supporting maintenance of macrophage efferocytosis and T helper 1/T helper 2 and T helper 17/ regulatory T cell balance. The failure of many anti-oxidation treatments indicates that ROS cannot be considered entirely harmful. Indeed, enhancement of ROS may sometimes be required. In a mouse model of rheumatoid arthritis (RA), absence of NOX2-derived ROS led to higher prevalence and more severe symptoms. In patients with RA, naïve CD4+ T cells exhibit inhibited glycolysis and enhanced pentose phosphate pathway (PPP) activity, leading to ROS exhaustion. In this “reductive” state, CD4+ T cell immune homeostasis is disrupted, triggering joint destruction, together with oxidative stress in the synovium.